The rainseekers - Kressel, Matthew (Tordotcom/Tor Publishing Group, 2026)
"Burned out and looking to put her past behind her, a former addict and recovering influencer interviews her fellow travelers en route to witness the first rain on Mars. Sakunja Salazar had it all. Money, toys, women, and all the drugs money could buy. A breakout Holo influencer, seemingly overnight she lifted her family out of their tiny Mexico City apartment and into the world of the rich and famous. That all changed when she hopped on a rocket and blasted into the cosmos, never to hawk lavender moisturizer again. What goes up must come down, and when Sakunja finally crashed back down on Mars an alcoholic, addict, and has-been she thought her life was pretty much over. That is, until a magazine editor discovered her photography and offered her a job. Now, she's the resident documentarian on a barebones expedition seeking to be the first humans to witness rain on Mars. For the first time in her life, Sakunja is turning the spotlight on someone else-interviewing her fellow travelers about what brought them to join this incredibly foolhardy crew of souls adrift in a world of danger and awe. And what they discover, both in their stories and their journey, will be more incredible than they could have ever imagined"-- Provided by publisher.